Effects of renal denervation on blood-pressure response to hemorrhagic shock in spontaneously hypertensive rats - Xiao-Na Cai; Chao-Yi Wang; Yuan Cai; Fang Peng (Chinese Journal of Traumatology, 2018)
Purpose: Renal denervation (RD) has been demonstrated to be an effective approach to reduce blood pressure for those with resistant hypertension. Yet, we aimed to explore the effect and possible mechanism of RD on blood-pressure response to hemorrhagic shock in spontaneously hypertensive rats. Methods: A total of 48 male spontaneously hypertensive rats were randomized to three groups: study group, sham-operation group and control group. RD was achieved by cutting off renal nerves and swabbing phenol on it. Ten weeks after RD, 8 rats in each group were sacrificed to collect the kidney and heart tissues. The remaining rats were subjected to an operation to induce hemorrhagic shock which would lead to 40% loss of total blood volume, and observed for 120 min. The serum concentration of norepinephrine was measured before and three weeks after RD. Results: The blood-pressure and norepinephrine levels were reduced significantly after RD (p < 0.05). Systolic blood pressure and diastolic blood pressure of the surgery group were higher than those in the sham and control groups at 15, 30 and 45 min after hemorrhagic shock (p < 0.05), while no significant difference was observed at 60, 90 and 120 min (p > 0.05). Additionally, the beta-1 adrenergic receptor (β1-AR) in the study group was significantly higher than those in the other two groups (p < 0.05) after hemorrhagic shock. Conclusion: This study demonstrated that RD could to some extent improve blood-pressure response to hemorrhagic shock in an established model of severe hemorrhagic shock in spontaneously hypertensive rats. The mechanism might be associated with up-regulation of β1-AR. Keywords: Renal denervation, Hemorrhage, Beta-1 adrenergic receptor, Spontaneously hypertensive rats